MEMIKIRKAN ULANG APLIKASI PENGINJILAN PRIBADI PADA MASA NEW NORMAL - Edwin Gandaputra (STT Saint Paul Bandung, 2021)
The Great Commission of The Lord Jesus in the gospel of Matthew is an important part of the misnistry of every person who follows Christ specifically for personal evangelism. The autor conducted research at four theological seminary, both S1 and S2. The Research results of all students (100%) agree with the importance of carrying out the mandate of the Lord Jesus through personal evangelism. The fact that all students pay attention to is 5% of students running is a personal evangelism (we call PI Pribadi) with inconsistencies. The Lord Jesus did not give The Great Commission contains coercion to His followers to go out to preach the Gospel of God. Jesus is King. But the Lord Jesus did not give orders as King to His followers to go preach the gospel of God. Praying in evangelism is not coercion or obligation, but God’s involvement as the subject of the evangelist who give opportunity to be involved in evangelism. The word ‘go away’ has no command meaning. The writer is interested is describing rethingking about the word ‘go away’ not in understanding the command. Matthew explained in Matthew 18:16-20 give a new nuance that is the basic of a rethinking of the great commission and applies it in personal evangelism. Telling the gospel or good news to many people is not by coercion or obligation. A disciple of Christ telling the good news not by force or obligation, but with joy at being involved in the work of Christ, the Messiah. Amanat Agung Tuhan Yesus dalam Injil Matius merupakan bagian penting dalam pelayanan setiap orang pengikut Kristus khususnya penginjilan pribadi. Matius memaparkan kristologi dan komunitas kerajaan surga yaitu gereja yang didirikan Tuhan Yesus sebagai penggenapan janji-janji Allah. Penulis melakukan penelitian pada empat Sekolah Tinggi Teologi baik mahasiswa S1 maupun S2. Hasil penelitian dari seluruh mahasiswa (100%) setuju dengan pentingnya menjalankan Amanat Tuhan Yesus melalui penginjilan pribadi, tapi hanya 5% yang menjalankan penginjilan pribadi. Kenyataan yang memprihatikan adalah 5% mahasiswa menjalankan PI pribadi dengan inkonsistensi. Tidak dapat dipungkiri bahwa kata kerja dalam bentuk perintah memiliki makna kewajiban yang mengandung paksaan. Yesus adalah Raja. Tapi Tuhan Yesus tidak memberikan perintah sebagai Raja kepada pengikut-Nya untuk pergi memberitakan Injil Tuhan. Berdoa dalam penginjilan bukan keterpaksaan atau kewajiban, tapi keteribatan Allah sebagai subyek pemberitaan Injil yang memberi kesempatan untuk keterlibat dan pengikut Kristus dalam penginjilan. Kata ‘pergilah’ tidak memiliki makna perintah. Paparan pemahaman kristologi dalam Matius 28:16-20, kita mendapat nuansa baru yang menjadi dasar dari pemikiran ulang bagi Amanat Agung dan aplikasikan dalam penginjilan pribadi. Sehingga pengikut Kristus menjalankan Amanat Agung dengan sukacita sebagai ucapan syukur atas anugerah yang Tuhan Yesus berikan. Seorang murid Kristus memberikan kabar baik bukan dengan paksaan atau kewajiban, tapi sukacita karena dilibatkan dalam pekerjaan Kristus, Sang Mesias.